Dimensionamento e simulação de um sistema híbrido eólico-fotovoltaico para o acionamento de uma planta de dessalinização por osmose reversa - Ribeiro, Shakil Bonnet Jossub (2020)
This dissertation presents the sizing and simulation of a Wind - Photovoltaic (W-PV) Hybrid System (HS) to drive a Reverse Osmosis (RO) desalination plant (DP) programmed to operate in the period of 8 hours per day. The HS performance is analyzed under climatic data (solar irradiation and wind speed) typical of Petrolina and Parnaíba over a period of one year, represen- ting the Brazilian interior and coast respectively. The objective of the work is to demonstrate a methodology of technical - financial dimensioning for an RO plant powered by HS for brackish water desalination with a better cost / benefit ratio in the final price of m3 of drinking water produced. The HOMER software is used in the HS financial - technical dimensioning and the results are used to optimize the RO plant, considering the minimum cost per cubic meter (R$/m3 ) of produced potable water. In a second step, the WAVE software is used to simulate the RO plant, the main characteristics being the type of water, this being a well (brackish) with salinity of 1,500 mg/L and use of the ECO PRO-440i membrane suitable for ideal plant pressure and flow. The 200 W RO plant has a structure of 1 pressure vessel with 1 membrane, with a consumption of 9.79 kWh/m3 of water with 377.7 mg/L of salinity, to supply this load Petrolina and Parnaíba present an HS W-PV with Energy Cost (COE) of R$ 3.74 and 3.63 per kWh, resulting in a Specific Production Cost (SPC) of R$ 33.95 and 32.96 per m3 respectively. For 2 kW load the Ro plant features a two-stage configuration, a structure of 1 pressure vessel with 1 membrane per stage, with a consumption of 6.02 kWh/m3 of water with 163,2 mg/L of salinity. To supply the second cargo Petrolina and Parnaíba has an HS W-PV with COE of R$ 0.82 and 0.81 per kWh, resulting in a CEP of R$ 5.33 and 5.27 per m3 respectively. Concluding that despite the approximate results, the configuration that brings the best cost / benefit ratio is the 2 kW RO plant in Parnaíba, a situation in which it provides a daily production of drinking water of 93.12 m3, presenting a specific competitive cost of R$ 5.27/m3 (R$ 0.105/20L), even lower than the costs of obtaining the input by other means, such as mineral water sold at R$ 187.50/m3 (R$3.75/20L) and water treated by tankers, sold at R$ 35.00/m3 (R$ 0.70/20L), on average.